Prenatal Evaluation of MicroRNA Expressions in Pregnancies with Down Syndrome. (24th March 2016) - Erturk, Biray; Karaca, Emin; Aykut, Ayca; Durmaz, Burak; Guler, Ahmet; Buke, Baris; Yeniel, Ahmet Ozgur; Ergenoglu, Ahmet Mete; Ozkinay, Ferda; Ozeren, Mehmet; Kazandi, Mert; Akercan, Fuat; et al.
Abstract : Background . Currently, the data available on the utility of miRNAs in noninvasive prenatal testing is insufficient in the literature. We evaluated the expression levels of 14 miRNAs located on chromosome 21 in maternal plasma and their utility in noninvasive prenatal testing of Down Syndrome. Method . A total of 56 patients underwent invasive prenatal testing; 23 cases were carrying Down Syndrome affected fetuses, and 33 control cases carrying unaffected, normal karyotype fetuses were included for comparison. Indications for invasive prenatal testing were advanced maternal age, increased risk of Down Syndrome in screening tests, and abnormal finding in the sonographic examination. In both the study and control groups, all the pregnant women were at 17th and 18th week of gestation. miRNA expression levels were measured using real-time RT-PCR. Results . Significantly increased maternal plasma levels of miR-3156 and miR-99a were found in the women carrying a fetus with Down Syndrome. Conclusion . Our results provide a basis for multicenter studies with larger sample groups and microRNA profiles, particularly with the microRNAs which were found to be variably expressed in our study. Through this clinical research, the utility of microRNAs in noninvasive prenatal testing can be better explored in future studies.